Peran Citra Merek Dan Kepercayaan Merek Dalam Mewujudkan Loyalitas Merek Pelanggan KFC - Rismadian, Ivana Azahra; -, Nurhadi (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2021)
Realizing brand loyalty is very important for the company so that the brand continues to be known and firmly entrenched in the minds of consumers. KFC is a well-known brand as well as a pioneer of fast food restaurants in Indonesia. This study aims to determine the effect of Brand Image and Brand Trust on Brand Loyalty. This type of research is quantitative using a data collection method with a questionnaire. The research sample was 385 respondents who made purchases at least twice in a period of one year at KFC in Surabaya who were drawn using purposive sampling technique. Information was collected using a questionnaire. The analysis technique used is Multiple Linear Regression using the SPSS 16 application. The results showed that simultaneously Brand Image and Brand Trust have a significant effect on Brand Loyalty. Partially, Brand Image and Brand Trust have a positive and significant effect on Brand Loyalty.